(untitled) (Al-Qamar, 2025)
Islam, which is a divine religion, strictly prohibits its followers from showing off their lineage. The present study intends to highlight the superiority of racial identity on language shifting from Balochi to Saraiki regarding the aspect of multi-lingual and multi-ethnic regions diversity in the population of Dera Ghazi Khan District. Identity is recognized as an important challenge of the present age. This study is qualitative in nature with the historic method and this research paper is essentially an analytical study of the identities of people with a mixed culture who simultaneously claim to be Baloch and speak Saraiki. The data were collected by using field surveys, interviews and participant observation. The researcher analyzed the data by employing an analytical approach. This study concludes that it is quite clear that the process of identity moves from individual to collective and the philosophy of survival is a fundamental aspect. The majority of the Baloch have adopted Saraiki language but they call and identify themselves as the Baloch. Because the distribution of resources in the state is not a criterion for people to come to their super identity, they use their regional or ethnic identity as superiority over their peers and others. The other bitter fact is that Baloches seem inflexible about that the nation is not made of them, but the language is part of the culture. So, the summary of this article is that the Saraiki-speaking Baloch even today introduce themselves ethnically as family pride.